Membangun Sistem Inventory Berbasis Web Menggunakan Metode Extreme Programming Studi Kasus Toko Lestari - Imam Sholikhin; Sewaka (CV. Multi Kreasi Media, 2022)
The sophistication of computer technology that is growing rapidly can make it easier for these companies to improve work efficiency, because work done with computers can save both in terms of time, space, energy, costs and others. As is the case with Toko Lestari, which is engaged in the distribution of basic food materials, it has not been optimal in meeting the information needs of information in an optimal manner where the data collection and reporting process for goods inventory is still carried out by recording in the ledger. at risk of data loss and data corruption. So in this research, an inventory system modeling will be carried out for the inventory process at Toko Lestari which produces the amount of stock items, reports on inventory data, inputs in and out of goods. With this information system, inventory management becomes more effective and efficient, search for inventory/stock information and reports is also more accurate and faster.